Comparison of ketamine/propofol (ketofol) and etomidate/fentanyl (etofen) combinations for procedural sedation and analgesia in the emergency department: An observational study - SANRI, ERKMAN; AKOĞLU, HALDUN; KARACABEY, SİNAN (ELSEVIER SCIENCE BV, 2017)
Objectives: The primary aim of this study was to report the vital signs, hemodynamic parameters and pain scores of the patients who have received procedural sedation and analgesia (PSA) with either ketofol (combination of ketamine and propofol) or etofen (combination of etomidate and fentanyl) and compare the proportion of patients with airway or respiratory adverse events (AEs) requiring an intervention and calculate the relative risk of AEs with each combination. Methods: This study is a prospective observational study with survey analysis. All patients received procedural sedation and analgesia (PSA) with either ketofol (combination of ketamine and propofol) or etofen (combination of etomidate and fentanyl) were prospectively observed. Vital and hemodynamic parameters and pain scores of the patients were recorded by automated equipment and visual analog scale (VAS) charts. Results: 112 patients were enrolled, 55 received ketofol and 57 received etofen. All patients with a respiratory AE (n = 27) observed to receive a respiratory intervention. Respiratory AE rate and proportion of patient who required a respiratory intervention were significantly higher with ketofol (p = 0.0029). Overall AE rate, and rates of desaturation, emergence reaction were also significantly higher in ketofol group. Conclusion: Etofen is a promising combination for the PSA of adult patients with lower respiratory AE and intervention rates and with better hemodynamic profile. Copyright (C) 2017 The Emergency Medicine Association of Turkey. Production and hosting by Elsevier B.V. on behalf of the Owner.
Keywords: Procedural sedation; Emergency department; Ketamine; Etomidate; Fentanyl; Propofol; DOUBLE-BLIND TRIAL; KETAMINE-PROPOFOL; RANDOMIZED-TRIAL; CLINICAL-TRIAL; CARDIOVERSION; FENTANYL; MIDAZOLAM; ADULTS